ANALISIS POTENSIALITAS EKONOMI DAN KETIMPANGAN WILAYAH DI KABUPATEN SUMEDANG - Endah Djuwendah (Paspalum: Jurnal Ilmiah Pertanian, 2016)
economic development. In addition, high income inequality also shows the heterogeneity between regions, as seen in Bekasi regency with a rapid growth rate. This research purposes were  to identify  the sector which is a base in the region growth, the economic structure change in each district, and  measure the level of regional inequality in Sumedang regency. This research design was descriptive qualitative and methods chosen was survey  with an analytical unit of 26 districts in Sumedang regency and its object are regional income (GDP), populations and the GDP is based upon the labor fields of each district during 2008-2012. The analysis tool used is Location Quotient, Classical Shift Share, and Williamson Index.The research results showed that The  region with a growth rate and higher competitiveness of other regions were  Jatinangor, Cimalaka, North Sumedang, , Sumedang south, Cimanggung, Paseh, Tanjungsari and Pamulihan. Four sectors have growth that is slower than the average growth of all sectors were agriculture, mining/quarrying, manufacturing and services.  Total Change  growth and the highest shift to agriculture occurred in the District Buahdua, mining / quarrying in District Paseh, the manufacturing sector in Sumedang District of northern sector of electricity, gas, water and buildings in the District Jatinangor sector trade, hotels and restaurants in the District of Sumedang Utara, transport, communications, finance, leasing, and services companies in the District of South Sumedang and services sectors in the District Jatinangor. Changes in total with the highest positive values contained in five sub-districts Jatinangor, North Sumedang, Cimanggung, South Sumedang and Tanjungsari. There was a transformation of the economic structure of Sumedang from the primary sector to the secondary and tertiary sectors. Potential sectors that become leading sector, made a great contribution because it has advantages kompetitif and comparative , be able to specialize in rural areas was  agriculture while urban areas was manufacturing, trade, hotels and restaurant and the services. Inequality of income distribution Sumedang  was relatively low (0,2-0,5) and the regional disparity in Sumedang including moderate with relatively stable inequality index value of 0.44.